Emsian (Lower Devonian) Polygnathids (Conodont) succession in the Spanish Central Pyrenees - Martínez-Pérez, C.; Valenzuela-Ríos, J.I.; Navas-Parejo, P.; Liao, J.-C.; Botella, H. (Journal of Iberian Geology, 2011)
A comprehensive conodont study of five sections of Emsian age, carried out in the Spanish Central Pyrenees, has revealed an important succession of polygnathids that can be used for identifying basal boundaries of globally recognized biozones. This succession consists of Polygnathus excavatus excavatus, Po. gronbergi, Po. nothoperbonus, Po. mashkovae, Po. laticostatus, and the new species Polygnathus luciae that allows the identification of the excavatus, nothoperbonus and laticostatus Zones. The nothoperbonus Zone is further subdivided into Lower and Upper nothoperbonus subzones, relying upon the lowest occurrence of Po. mashkovae. These biostratigraphic data from the Spanish Central Pyrenees corroborate the succession of conodont indexes in other regions of Europe (north-western France and southern Italy), North Africa (Morocco), Central Asia, Australia, and North America (Alaska, Nevada and Canada).